Designing gardens with flora of the American East - Summers, Carolyn, 1954- (Rutgers University Press, 2010)
The beautifully illustrated Designing Gardens with Flora of the American East approaches landscape design from an ecological perspective, encouraging professional horticulturalists and backyard enthusiasts alike to intensify their use of indigenous or native plants. These plants, ones that grow naturally in the same place in which they evolved, form the basis of the food web. Wildlife simply cannot continue to survive without them-nor can we. Summers provides guidelines for * The best ways to use exotic and nonindigenous plants responsibly * Easy-to-follow strategies for hosting butterflies, bees, moths, birds, and fish * Designs for traditional gardens using native trees, shrubs, vines, grasses, perennials, fruiting plants, and groundcovers as substitutes for exotic plants * How to control plant reproduction, choose cultivars, open-pollinated indigenous plants, and different types of hybrids.